A gold nanoflower-based traceable drug delivery system for intracellular SERS imaging-guided targeted chemo-phototherapy. Issue 19 (25th April 2018) - Song, Chunyuan; Dou, Yanxia; Yuwen, Lihui; Sun, Youzhi; Dong, Chen; Li, Fang; Yang, Yanjun; Wang, Lianhui
Abstract : A novel traceable and targeted drug delivery nanosystem with high drug encapsulation and pH-controlled release was prepared based on gold nanoflowers for efficient intracellular SERS imaging-guided chemo-phototherapy. Abstract : Accurate and effective drug delivery in tumor cells significantly improves the curative effect with high drug delivery efficiency, low toxicity and side effects and has become an urgent demand for anticancer therapy. In this paper, a novel traceable and targeted drug delivery nanosystem ( i.e. AuNF-nanocarriers) with high drug encapsulation and pH-controlled release was prepared based on gold nanoflowers (AuNFs) for efficient intracellular SERS imaging-guided chemo-phototherapy. SERS-active flower-like gold nanoparticles with large surface area were synthesized first and then modified with Raman and RGD molecules in sequence to prepare bright, traceable and targeted SERS tags of A549 human lung cancer cells. Furthermore, thiolated-PAA (PAA-SH) was synthesized and utilized for the first time to modify the SERS tags with a layer of negative charges for efficient pH-dependent loading and release of the anticancer drug doxorubicin. Based on the A549 human lung cancer cell model, the availability of the proposed AuNF-nanocarriers for efficient intracellular SERS imaging-guided chemo-phototherapy was studied and the results indicate that the AuNF-based drug delivery system exhibited attractive characteristics such as good stability, efficiency and pH-controlled drug loading and release, traceable and targeted delivery, as well as SERS imaging and chemo-phototherapy functions, and shows great potential for powerful SERS-imaging and as a theranostic candidate for precision nanomedicine that could achieve sensitive and accurate tumor detection and therapy.